Significant enhancement of bromate removal in drinking water: Implications for the mechanism of sonocatalytic reduction - Cui, Mingcan; Choi, Jongbok; Lee, Yonghyun; Ma, Junjun; Kim, Dukmin; Choi, Jaeyoung; Jang, Min; Khim, Jeehyeong (ELSEVIER SCIENCE SA, 2017)
Bromate (BrO3-) is a potential carcinogenic compound that can form during the disinfection of drinking water. For the first time, the sonocatalytic reduction of BrO3- were studied through examining the effect of the important operational parameters such as ultrasound (US) frequency, TiO2 loading, pH, temperature and other anions. By observing sonoluminescence (SL) at various frequencies and measuring H-2 production rates, a new reduction mechanism for BrO3- is also proposed. The kinetic results presented that the BrO3- reduction rates enlarged as the measured H-2 production rate increased for all parameters, and the slopes between the BrO3- reduction and H-2 production rates for sonocatalysis were much higher than those for sonolysis. Interestingly, sonolysis could be limited by the amount of H-2 production, but sonocatalysis could increase the BrO3- reduction rate because of additional electrons (e(-)) from the surface of TiO2 via SL. The highest SL intensities for H-2 production and BrO3- reduction rates occurred at an ultrasound frequency of 500 kHz, implying that an increase in SL intensity caused by ultrasound cavitation enhanced H-2 production and increased the a released to the conduction band of TiO2. At 500 kHz, BrO3- reduction rate (6.84 x 10(-2) min(-1)) by sonophotocatalysis was 5.2 times higher than that (1.32 x 10(-2) min(-1)) of sonolysis. Investigation into the effect of anion species showed that BrO3- reduction was inhibited or enhanced depending on the type of anions present. In real application, sonocatalytic reduction of BrO3- could be advantageous, as it has higher reduction rates than those reported for photocatalysis. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: ZERO-VALENT IRON; PHOTOCATALYTIC REDUCTION; CATALYTIC-REDUCTION; HYDROGEN EVOLUTION; AQUEOUS-SOLUTION; DECOMPOSITION; IRRADIATION; BICARBONATE; ADSORPTION; REACTIVITY